2021
DOI: 10.6061/clinics/2021/e2580
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios before and after percutaneous coronary intervention and their impact on the prognosis of patients with acute coronary syndrome

Abstract: OBJECTIVES: This study aimed to prospectively observe the changes in the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) before and after percutaneous coronary intervention (PCI) and their impact on the prognosis of patients with acute coronary syndrome (ACS). METHODS: Blood samples from 205 patients with ACS were collected at admission and at 24h and 30 days post-PCI to observe changes in the complete blood count. The Cox multivariate regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Simultaneously, NLR increased significantly the day after admission ( Figure 3 ). In this case, the NLR recorded the day after admission was 11, notably higher than the reported average NLR of 4.5 within the first 24 h following AMI [ 21 ]. As PCI can also cause an inflammatory response, a marked increase in CRP level and NLR on the day after revascularization can be a good indicator of the early detection of mechanical complications [ 22 ].…”
Section: Discussionmentioning
confidence: 59%
“…Simultaneously, NLR increased significantly the day after admission ( Figure 3 ). In this case, the NLR recorded the day after admission was 11, notably higher than the reported average NLR of 4.5 within the first 24 h following AMI [ 21 ]. As PCI can also cause an inflammatory response, a marked increase in CRP level and NLR on the day after revascularization can be a good indicator of the early detection of mechanical complications [ 22 ].…”
Section: Discussionmentioning
confidence: 59%
“…Sheng et al found that the neutrophil count and proportion at 24 hours after PCI in patients with ACS were significantly higher than those before PCI, while platelet and lymphocyte counts were significantly decreased. 33 Additionally, a recent study also reported that the absolute counts of neutrophils, intermediate monocytes and CD4 + (helper) T cells were significantly increased in the depressed group. 34 In view of that decreased lymphocyte and increased neutrophil count are both found in post-PCI patients and depression subjects, which might partly explain the increased NLR levels observed in post-PCI depression patients.…”
Section: Discussionmentioning
confidence: 94%
“…The analysis of the receiver operating characteristic (ROC) curve indicated that the NLR measured at 24 h after PCI demonstrated superior predictive ability for the occurrence of MACE. There was a significant correlation observed between the NLR at 24 h after PCI and the quantity and length of stents implanted, as well as the duration of the procedure [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The number and length of stents inserted, the duration of the operation, were significantly correlated with the NLR at 24 h following PCI, increasing the risk of recurrent ischemic episodes [ 19 , 20 , 23 ].…”
Section: Figurementioning
confidence: 99%